Toward Peaceful Dialogues; Sunni, Shi’a and Ahmadiya: An Effort to Build Inclusivity and Theological Awarness in Contemporary Indonesia - Barsihannor Barsihannor (Al-Hikmah Journal for Religious Studies, 2023)
The violence due to theological issues, especially as experienced by Shi’a and Ahmadiya in Indonesia suggests that religious sensitivity in a modern and democratic society is still a latent danger for the emergence of theological conflict in Muslim society. Even though they are in the same house (Islam) and referring to the same holy book, however, the reality shows that horizontal conflicts due to theological interest still occur and even pose a threat to religious life. Theological reasons are used as arguments to terrorize, attack, and eliminate other groups who are regarded differently. This research intends to reveal the common ground of the three theological schools, the impact of theological conflict, and to describe the role of the Indonesian government and society to create a conducive atmosphere in religious life.